Lung cancer presenting with central nervous system metastasis: Clinicopathological and molecular analysis of 171 cases - Demleitner, Madeleine; Erlenbach-Wünsch, Katharina; Coras, Roland; Erber, Ramona; Polifka, Iris; Eyüpoglu, Ilker Yasin; Fuchs, Florian; Hartmann, Arndt; Agaimy, Abbas (Annals of Diagnostic Pathology, 2023)
A subset of lung carcinoma presents initially with brain metastasis. Precise subtyping is mandatory for optimized treatment of these advanced aggressive carcinomas. We herein analyzed surgical biopsies from 171 Patients (99 males and 72 females aged 48–96; mean, 72), who presented with brain metastasis of lung cancer. In addition to conventional subtyping, we applied an extended immunohistochemistry (IHC) panel and performed several molecular tests looking for potential therapeutic targets other than EGFR mutations. Non-small cell carcinoma (NSCLC) comprised 157 (91.8 %) of cases: 109 (63.7 %) adenocarcinomas, 27 (15.8 %) squamous cell (SCC), 18 (10.5 %) large cell undifferentiated, 1 (0.6 %) adenosquamous and 2 (1.2 %) unclassified carcinomas. Of the adenocarcinomas, 81.7 % were TTF1+. Notably, 45 % of those TTF1-negative cases expressed HepPar1. SMARCA4 and SMARCA2 loss was observed in 13/171 (7.6 %) and 32/163 (19.6 %) cases, respectively; mainly TTF1- (40.0 %) and HepPar1+ (38.1 %) adenocarcinomas were affected by SMARCA2/4 loss. Loss of at least one mismatch repair (MMR) protein was observed in 3/156 (1.9 %) cases (2 adenocarcinomas and 1 large cell neuroendocrine carcinoma/LCNEC). Limited available data on mutation testing showed a frequency of EGFR mutations of 4.3% and of KRAS mutations of 57%. HER2 expression (2+/3+) was found in 45/166 (27.1 %) of cases with amplification verified by CISH in 18/38 (47.4 % of immunopositive cases and 10.5 % of the whole cohort); all but one were adenocarcinomas. Other genetic abnormalities detected included EML4::ALK rearrangements in 3 (1.8 %; 2 TTF1+ adenocarcinomas and 1 LCNEC) and RET rearrangements in one SCNEC. Variable subsets of tumors revealed amplifications of several potentially therapeutically targetable genes including MYC (30.0 %), MET (10.1 %), HER2 (10 %), FGFR1 (9.6 %), FGFR3 (4.6 %), and FGFR2 (3.4 %). This study highlights a highly heterogeneous molecular background in lung cancer presenting with CNS metastases. These findings highlight the need for individualized tumor testing strategies looking for potential therapeutic targets for this aggressive disease.
CRIS-Team Scopus Importer:2023-01-27
Keywords: ALK; Central nervous system metastasis; Immune therapy; Microsatellite instability; NSCLC; SMARCA4